Neurology residency training in 2017: A survey of preparation, perspectives, and plans. (8th January 2019) - Mahajan, Abhimanyu; Cahill, Carolyn; Scharf, Eugene; Gupta, Sahil; Ahrens, Stephanie; Joe, Elizabeth; Schneider, Logan
Abstract : Objective: To survey graduating US neurology residents on the topics of debt, fellowship interview process, future plans, and their readiness for practice and business management tasks. Methods: An electronic survey was sent to all US American Academy of Neurology member adult and child neurology residents graduating in June 2017. Results: The response rate was 23.4% (n = 159). Of the 143 residents who provided information about student loans, 57% reported having debt (median $180, 000). Ninety percent of respondents reported plans to pursue a fellowship after residency; 57% intended to stay at their home institution for additional training. Among respondents from adult neurology programs, 87% preferred to begin the fellowship application process after the first 6 months of the third postgraduate year. Almost half (46%) of adult neurology program residents felt they did not have enough outpatient exposure prior to making fellowship decisions compared to 14% of child neurology trainees. Although reported readiness to perform specific tasks (coding and office management) increased since 2007 ( p < 0.05), only 36% of all respondents reported receiving business management training during residency. Conclusion: Trainees completing residency report considerable educational debt. A large majority of residents feel the fellowship application process occurs too early. Despite improvements over recent years, the majority of residents continue to feel ill-prepared for specific practice management tasks. These results suggest a need to better understand the effect of educational debt on career choices, an examination of the timing of the fellowship application process, and the incorporation of additional business management training during residency.